2020
DOI: 10.1371/journal.pone.0228685
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the vestibular system in obesity and impaired glucose metabolism in high-fat diet-fed mice

Abstract: The vestibular system controls balance, posture, blood pressure, and gaze. However, the roles of the vestibular system in energy and glucose metabolism remain unknown. We herein examined the roles of the vestibular system in obesity and impaired glucose metabolism using mice with vestibular lesions (VL) fed a high-sucrose/high-fat diet (HSHFD). VL was induced by surgery or arsenic. VL significantly suppressed body fat enhanced by HSHFD in mice. Glucose intolerance was improved by VL in mice fed HSHFD. VL blunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…17 Vestibular stimulation was 18 Animal studies have demonstrated a decrease in body weight followed by caloric vestibular stimulation. 6,7 Human studies also reported regulation of lipid profile followed by vestibular stimulation. 19,20 The present study results support earlier studies as there is a decrease in the body weight of the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Vestibular stimulation was 18 Animal studies have demonstrated a decrease in body weight followed by caloric vestibular stimulation. 6,7 Human studies also reported regulation of lipid profile followed by vestibular stimulation. 19,20 The present study results support earlier studies as there is a decrease in the body weight of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…6 Vestibular dysregulation was reported to influence obesity and vestibular stimulation was reported to alter the set point of fat. 7,8 Although there are multiple methods available to stimulate the vestibular system, optimal stimulation is required to avail maximum beneficial effects. Electrical vestibular stimulation is a simple and non-invasive method and can control the strength of the stimulation offered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vestibular stimulation plays an important role in food intake [40]. Obesity is observed in DM due to insulin resistance.…”
Section: Vestibular Exercise and Yogic Diet In Diabetesmentioning
confidence: 99%
“…We pointed out that that the vestibular system appears to play a key (though much underrecognized) role in metabolic homeostasis. This is reflected neuroanatomically by vestibular projections to multiple brainstem and hypothalamic nuclei involved in the central control of metabolism, including: the central melanocortin system (CMS) that is involved in appetite regulation and fixing a set-point for body fat; major parasympathetic sites; and centers that regulate brown adipose tissue (BAT) [1][2][3].…”
Section: Main Textmentioning
confidence: 99%